Decriminalization of drug dependants / Afiq Akmal Zainal Abidin … [et al.] - Zainal Abidin, Afiq Akmal; Ismail, Nurulizma; Zainolabidin, Nurul Akhyar; Zarawi, Nurhidayah (2014)
The illegal abuse of drugs remains as a serious problem in Malaysia. Over the decade, a various effort had been made by the government to curb the drugs menace. However, this problem had not come to the ends yet despite of the criminalization approach taken by Malaysia. Thus, this research is to suggest the decriminalization of drugs dependant as a new approach to settle this problem. This research has five chapters. The first chapter consists of the introduction and research backgrounds which explain about the meaning of drugs, the law in relation with drug in Malaysia and in comparison with the law of drug in Portugal and Australia. Apart from that, it also contains the objective, problem statement, research methodology, scope of research, and limitations of research that we encounter in doing this research. Generally, Chapter 2 is the literature review about the drugs law in Malaysia and the problem with the existing law was also highlighted. While in Chapter 3 consists of the law review on the law in Portugal and Australia. As these countries was used as a reference to the decriminalization approach that had been exercise and produce the good result in connection with the drugs problem. Basically, what was provided in the Chapter 4 is the result of research finding. This result was produced after the conducting the interview with a few respondents. In chapter 5, there were a few recommendations to shift our current criminalization approach to the decriminalization approach as practice by Portugal and Australia. It also suggests an amendment of the current law to achieve a better country with a lower drugs abuse problem.